Analysis of Financial Standing in Joint-Stock Companies of Telecommunications Sector - Grabowska, M. (Электронное моделирование, 2009)
Main focus of this work is to present the results of empirical investigations of financial standing in joint-stock companies from telecommunications sector. The analysis was carried out on the basis of the following ratios: liquidity, return and debt ratio. The second part of the investigations encompassed empirical analysis based on relationships between price and book value.